2019
DOI: 10.15640/jeds.v7n3a1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foreign Multilateral Aid and Foreign Bilateral Aid on Capital Formation in Kenya

Abstract: Low capital formation in Kenya, averaging rate 20.13% of GDP over the period 2006-2017 has kept unemployment rate above 39% with more than 65 per cent of people living on less than $ 2 a day. Yet previous studies do not have a clear answer to the question of whether increasing bilateral aid/multilateral aidenhances capital formation or not. This study's purpose was to investigate the effect of multilateral aid and bilateral aid on capital formation in Kenya. The study was anchored by Solow (1956) model. Autore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Mallik (2008) revealed that FA negatively impacts national economic growth in the long run by assessing 35 years in six African countries. Wafula, Odondo and Obange (2019) revealed an insignificant contribution to economic development in the short and long run during 1974-2017 in Kenya. These results have been confirmed by Bird and Choi (2020), showing a more ambiguous impact of FA.…”
Section: Related Literaturementioning
confidence: 98%
“…Mallik (2008) revealed that FA negatively impacts national economic growth in the long run by assessing 35 years in six African countries. Wafula, Odondo and Obange (2019) revealed an insignificant contribution to economic development in the short and long run during 1974-2017 in Kenya. These results have been confirmed by Bird and Choi (2020), showing a more ambiguous impact of FA.…”
Section: Related Literaturementioning
confidence: 98%
“…Based on this finding, the formulation of appropriate policy that can encourage more inflows of aid was recommended. In Kenya, Wafula et al (2019) used unconstrained model to study the role of ODA in capital formation and economic growth, during the period 1974-2017. The results revealed Economic growth in sub-Saharan Africa insignificant positive effect in the short-run and long-run, which suggest the need to encourage development aid through appropriate policy measures.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Based on this finding, the formulation of appropriate policy that can encourage more inflows of aid was recommended. In Kenya, Wafula et al. (2019) used unconstrained model to study the role of ODA in capital formation and economic growth, during the period 1974–2017.…”
Section: Literature Reviewmentioning
confidence: 99%